Considerations on the Breeding and Weaning of Buffalo Calf - Zicarelli, Luigi (Journal of Buffalo Science, 2020)
The buffalo calf is more challenging to adapt to the transition from breast milk to other substitutes that favor weaning. Growth in the pre-weaning period is affected by the amount of reconstituted milk consumed. When the quantity of reconstituted milk consumed is low, the weaning weight is also low. The gap between the latter and the optimal weight will never be eliminated because the species cannot perform compensatory growth, such as cattle. There is a delay in reaching an optimal live weight to start puberty. The age at first birth is, in fact, lower in those countries that leave all the milk to the calf for meat production or as happens in Italy where there is a suitable milk substitute. In Italy, it has been verified that calves taking almost ad libitum quantities of cow's milk weigh more than 140 kg at 4 months and have their first birth at the age of 22-26 months. As adults, they have an almost zero percentage of vaginal or uterine prolapse. In further experiences on 3672 heifers, it was possible to verify "ex-post" that the calves that had taken a more significant quantity (150 kg vs. 105) of milk substitute had shown age at the first birth in advance of about 6 months (28, 5 versus 34). Future investigations should verify the effect of weaning birth and not just the cost of weaning. Age at first birth is not only an economic parameter, but it is useful for an early evaluation of bulls in progeny tests.